Proposal for a consortium plan involving the La Salette Schools of Isabela - Javier, Clarita R. (Animo Repository, 1979)
This study attempts to present a consortium plan involving the La Salette Schools of Isabela specifically on the following areas: organization, administrative meetings, faculty development through in-service training, sharing of experts, and joint socio-cultural activities for the first year of operation. Plan for the next five years include the following: administrative meetings, faculty sharing, faculty development, joint use of facilities, research, students exchange, common grading system, joint socio-cultural activities, cooperative purchasing, off-campus training, supervision of instruction, and joint publication of the La Salette Schools student paper. This study used the descriptive survey method. Data were gathered through visitation and observation of the La Salette Schools, personal interviews of the school heads and the responses to the checklist and questionnaire. The administrative manual of La Salette College and the faculty handbook of La Salette of Santiago provided the historical background and philosophy of education of the La Salette Schools of Isabela. The findings show that: 1) financing is the number one problem of the La Salette Schools. Other problems are inadequate facilities, evaluation of teachers, discipline of students and relationship 2) the idea of a consortium among the La Salette Schools of Isabela was accepted by the school heads 3) it is feasible to organize a consortium among the La Salette Schools of Isabela 4) by choice of priority, the principals desired to improve and update the teachers through faculty development programs and 5) it is not possible to implement the standardization of salaries due to differences in financial capabilities of the schools. However, this should be studied by the principals for recommendation to the La Salette Board of Trustees.